Social factors of communicative misunderstanding between forced migrants and the host community - Popova, Olga (Technium Social Sciences Journal, 2020)
This paper examines social factors that cause misunderstandings between forced migrants and members of a host community. The article investigates mechanisms of social perception as a process responsible for quality of communication between these actors, as well as the relationship of these mechanisms with integration of forced migrants into the host society. The article presents the results of two studies: in the first one, 318 interviews with forced migrants from Donbass were got in 2018, and, in the second one, 200 interviews were obtained in 2019. The studies have demonstrated a high level of prejudice of the host society towards forced migrants, low level of generalized trust of migrants to surrounding people. This situation contributes to the formation of bonding social capital, but does not contribute to the formation of bridging and linking capital, which does not affect the expansion of new social connections and the acquisition of new relevant social capital.